2021
DOI: 10.3390/biom11091271
|View full text |Cite
|
Sign up to set email alerts
|

Growth Suppression in Lung Cancer Cells Harboring EGFR-C797S Mutation by Quercetin

Abstract: Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are approved treatments for non-small-cell lung cancer (NSCLC) patients harboring activating EGFR mutations. The EGFR C797S mutation is one of the known acquired-resistance mutations to the latest third-generation TKIs. At present, there are no clear options for treating patients who acquire resistance to third-generation TKIs. The acquisition of the EGFR C797S mutation was shown to upregulate the expression of AXL, a receptor tyrosine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Qu is an effectual inhibitor for managing NSCLC harboring the EGFR C797S mutation. However, Qu displayed promising cytotoxic results on NSCLCs harboring the EGFR C797S mutation via preventing AXL and stimulating cell death (316). It mimics the interfaces of ATP in the active location of RTKs (EGFR, FGFR1, and c-Met) that lead to the prevention of C RTK overexpression (317).…”
Section: Effect Of Quercetin On the Egfr-mediated Pathwaymentioning
confidence: 99%
“…Qu is an effectual inhibitor for managing NSCLC harboring the EGFR C797S mutation. However, Qu displayed promising cytotoxic results on NSCLCs harboring the EGFR C797S mutation via preventing AXL and stimulating cell death (316). It mimics the interfaces of ATP in the active location of RTKs (EGFR, FGFR1, and c-Met) that lead to the prevention of C RTK overexpression (317).…”
Section: Effect Of Quercetin On the Egfr-mediated Pathwaymentioning
confidence: 99%
“…In this study, we analyzed the major components of FYLM using UPLC-Q-Orbitrap-MS and identified 36 chemical constituents. Among them, it has been reported that quercetin, scutellarin, oleanolic acid, apigenin and formononetin can overcome acquired resistance to EGFR-TKIs by inhibiting proliferation, promoting apoptosis and inducing autophagy in vitro and in vivo ( Chen et al, 2019a ; Chen et al, 2019b ; Yu et al, 2020b ; Huang et al, 2021 ; Sun et al, 2021 ). For example, quercetin reduced the growth of EGFR-C797S mutated NSCLC cells via inhibiting ALX and promoting apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Quercetin displayed its significant cytotoxicity on the viability and growth of human NSCLC cells. [ 23 ] Studies have shown that quercetin exerted its therapeutic effect on NSCLC cells by inhibition of proliferation, suppression of migration and the enhancement of apoptosis. [ 24 , 25 ] It has also been reported that quercetin delivered superior anticancer activity in NSCLC-bearing mice model by biotinylated mixed micelles.…”
Section: Discussionmentioning
confidence: 99%